Hepatic veno-occlusive disease: pathogenesis, diagnosis and treatment - Wadleigh, Martha; Ho, Vincent; Momtaz, Parisa; Richardson, Paul (Current opinion in hematology, 2003)
Hepatic veno-occlusive disease (VOD) is one of the most serious complications following hematopoietic stem cell transplantation (SCT) and is associated with a very high mortality in its severe form. This review outlines the pathogenesis and clinical features of VOD, with an emphasis on endothelial cell injury and risk factors. The current status and future directions of research for both prophylaxis and treatment are also discussed.